From the War of Independence to the Mechanized Warfare: Turkish Land Doctrine and Its Discussions During the Interwar Period (1923-1939) - Efe Güzeloğlu (Yakın Dönem Türkiye Araştırmaları)
This work explores Turkish land doctrine during the interwar period. Particular attention is given to its roots, its evolution during the interwar years, how it faced the challenge of modern mechanized warfare, and the effects of the first lessons of World War II. The article’s main purpose is to investigate the response of a relatively underdeveloped army to the rise of modern military technologies. It will be shown that the Turkish army focused excessively on its past achievements, which resulted in the revolutionary effects of new military technologies being underestimated. While the Turkish General Staff and officers were “preparing for the last war,” mechanization had completely transformed modern warfare. Methodologically, this work cross-reads official sources on Turkish military doctrine with personal opinions expressed by Turkish officers on the subject.